Effect of different splitting forms of nitrogen fertilization in sugarbeet - Hemp, Silmar; Cordeiro, Daltro Silva; Porto, Marilda Pereira; Brauner, Jorge Luiz; Junior, Paulo Silveira (Pesquisa Agropecuaria Brasileira, 2014)
A sugarbeet (Beta vulgaris L.) field experiment was carried out in the experimental area of EMBRAPA/UEPAE of Pelotas, during the 1981/82 crop season. Twelve treatments comprising different forms of splitting the application of 200 kg/ha of N were allocated to a randomized block design, with four replications. The sugarbeet variety was the multigerm Trirave. Regarding the root yield, dry matter and nitrogen accumulation, the results showed that splitting the application of nitrogen resulted in higher yields than a single dose at seeding. Nitrogen distribution up to 60 or 90 days after emergence showed better results than those at 30 days after emergence. The fermentable sugars concentration was not affected by the different forms of nitrogen splitting. The better time for roots harvest was estimated as being 185 days after emergence.